The Effect of Foot Massage Therapy in Controlling Blood Pressure in Elderly People with Hypertension in the Working Area of Puskesmas Buaran - Hudayah, Nur Laila; Arifiyanto, Dafid (Prosiding University Research Colloquium, 2023)
As we get older, the physiological function of the body decreases due to the aging process so that this condition causes various health problems. Health problems that often arise in the elderly are Non-Communicable Diseases (NCDs) such as hypertension. It is a condition in which the systolic blood pressure is ?140 mmHg and the diastolic blood pressure is ?90 mmHg with more than two measurements. Furthermore, it is also often well known as The Silent Killer considering it often appears with no complaining. For controlling it, foot massage therapy could be applied as complementary one. This study aims to determine the effect of foot massage therapy in controlling blood pressure in elderly people with hypertension.The sampling technique in this study used a purposive sampling technique with 10 respondents. The research is a quantitative study with a method of quasy experiment one group pretest-posttest design. In this study, the results of the t-dependent test showed a p-value of 0.001 for the systolic blood pressure and 0.001 for the diastolic blood pressure, so the value of p ? 0.05. It means there is a difference in blood pressure before and after therapy. Foot massage therapy is able to control blood pressure in the elderly with hypertension. Therefore, in addition to pharmacological therapy, elderly people with hypertension can also be advised to do foot massage therapy to control blood pressure.